Analisis Pengendalian Kualitas Presentase Olein RBDPL Utama Pada Proses Fraksinasi Di PT. Y Dengan Metode Statistical Quality Control - Maria Angelina Sitanggang; Sukanta Sukanta (Fakultas Teknik Universitas Tulang Bawang, 2023)
PT Y is one of the largest vegetable oil processor companies in Indonesia. In the process, palm oil processing produces 2 types of end products, namely RBDPS (Refined Bleached Deodorized Palm Sterin) and RBDPL (Refined Bleached Deodorized Palm Olein) which are the main results for cooking oil. This study aims to interpret the percentage data of RBDPL (yield) value using the Xbar – R control chart and analyze the 2 main divisions that play a role, namely Production and Quality Control, the cause of the non-conformity to the yield value that has been targeted by the company through fishbone diagrams. The results of this study indicate that the average RBDPL yield is only 55.92% while the company's target is 60% and the main causes of non-conformance are in humans, methods and machines. Keywords: RBDPL, Statistical Quality Control, Yield.